Readiness for Radiological and Nuclear Events among Emergency Medical Personnel - Dallas, Cham E.; Klein, Kelly R.; Lehman, Thomas; Kodama, Takamitsu; Harris, Curtis Andrew; Swienton, Raymond E. (Frontiers in Public Health, 2017)
Background Among medical providers, even though radiological and nuclear events are recognized as credible threats, there is a lack of knowledge and fear about the medical consequences among medical personnel which could significantly affect the treatment of patients injured and/or contaminated in such scenarios. This study was conducted to evaluate the relative knowledge, willingness to respond, and familiarity with nuclear/radiological contamination risks among U.S. and Japanese emergency medical personnel. Methods An institutional review board-approved anonymous paper survey was distributed at various medical and disaster conferences and medicine courses in Japan and in the U.S. The surveys were written in Japanese and English and collected information on the following four categories: generalized demographics, willingness to manage, knowledge of disaster systems, and contamination risks. Results A total of 418 surveys were completed and collected. Demographics showed that physicians and prehospital responders were the prevalent survey responders. The majority of responders, despite self-professed disaster training, were still very uncomfortable with and unaware how to respond to a radiological/nuclear event. Conclusion Despite some educational coverage in courses and a limited number of disaster events, it is concluded that there is a lack of comfort and knowledge regarding nuclear and radiological events among the medical community. It is recommended that considerable development and subsequent distribution is needed to better educate and prepare the medical community for inevitable upcoming radiological/nuclear events.